THE BENEFITS OF LI-ESWT THERAPY IN ORGANIC ERECTILE DYSFUNCTION WITH CHRONIC RENAL FAILURE: A CASE REPORT - Setiawan, Androniko; Japari, Andrian; Cakrasana, Haris; Agustinus (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2020)
Erectile dysfunction (ED) is a common type of male sexual dysfunction that has a negative impact on the quality of life. Erectile dysfunction is common in men and the incidence increases with age. Erectile dysfunction can be caused by organic disorders, such as hormonal disorders and metabolic disorders. In this case report, the authors report the case of a man who developed chronic renal failure with multiple metabolic disorders and hypogonadism. This case report described the benefits of Low Intensity Extracorporeal Shockwave Therapy (Li-ESWT) therapy in patients who less responsive after receiving phosphodiesterase type 5 inhibitor (PDE-5 inhibitor) therapy, tadalafil as first-line therapy for erectile dysfunction. This case report was evaluated using the International Index of Erectile Function-5 (IIEF-5) questionnaire and Erection Hardness Score (EHS) score as a description of erection quality with Peak Systolic Velocity (PSV) parameters from the results of penile Color Doppler Ultrasonography (CDUS) during flaccid and Vascular Endothelial Growth Factor (VEGF) parameters as angiogenesis factors. In this case report, the patient experienced improvements in erection quality, PSV parameters, and VEGF parameters after receiving Li‑ESWT therapy.